Impact of N₂+H₂ mixture plasma on carbon-containing film - Voitsenya, V.S.; Masuzaki, S.; Motojima, O.; Sagara, A.; Jacob, W. (Вопросы атомной науки и техники, 2006)
The short review is done of published data on impact of plasma produced in the N₂+H₂ mixture on carbon and organic films. It is concluded that such plasma can be much more effective in cleaning of the walls of fusion devices from a carbon-based contaminating deposit in comparison with plasmas of discharges in H₂, Ar or He.